A Parametric Model for the Allocation of Fire Companies in New York City - Rider, Kenneth Lloyd (Management Science, 1976)
A fire department, in order to balance equitably its resources throughout a city, must consider several often conflicting objectives. This paper describes an allocation method that avoids the difficulty of choosing an objective in advance by allowing the decision-maker to enumerate a range of criteria by varying a trade-off parameter. The method uses travel time to fires as a measure of system performance and generates allocations satisfying criteria ranging from the minimization of city-wide travel time to the equalization of average travel times in different regions. A comparison of the allocations generated by the model to the current allocation of fire companies in New York City shows that one value of the trade-off parameter produces results that correspond closely to the current allocation policy. An example of how the model can be used as a policy tool is given.